Inherent trait differences explain wheat cultivar responses to climate factor interactions: New insights for more robust crop modelling. (10th August 2020) - Eller, Franziska; Hyldgaard, Benita; Driever, Steven M.; Ottosen, Carl‐Otto
Abstract: Climate change predictions foresee a combination of rising CO2, temperature and altered precipitation. Effects of single climatic variables are well defined, but the importance of combined variables and genotypic effects is less known, although pivotal for assessing climate change impacts, for example, with crop growth models. This study provides developmental and physiological data from combined climatic factors for two distinct wheat cultivars (Paragon and Gladius), as a basis to improve predictions for climate change scenarios. The two cultivars were grown in controlled climate chambers in a fully factorial setup of atmospheric CO2 concentration, growth temperature and watering regime. The cultivars differed considerably in their developmental rate, response pattern and the parameters responsible for most of their variation. The growth of Paragon was linked to climatic effects on photosynthesis and mainly affected by temperature. Paragon was overall more negatively affected by all treatment combinations compared to Gladius. Gladius was mostly affected by watering regime. The cultivars' acclimation strategies to climate factors varied significantly. Thus, considering a single factor is an oversimplification very likely impacting the accuracy of crop growth models. Intraspecific crop variation could help understanding genotype by environment variation. Cultivars with high phenotypic plasticity may have greater resilience against climatic variability. Abstract : We investigated responses of two wheat cultivars (Paragon and Gladius) to multiple climate change factor combinations of watering, temperature and CO2 . The cultivars differed in their developmental rate and response pattern: the growth of Paragon was linked to climate effects on photosynthesis and mainly affected by temperature, while Gladius was mostly affected by watering regime. Our study emphasizes cultivar‐dependent response strategies and provides data for predicting crop growth with models under climate change scenarios. As wheat is one of the most important food crops, breeding to withstand interacting climate factors could mitigate the impact of climate change on wheat yield.